Investigation of Teachers' Knowledge Management and Knowledge Hiding Behaviors - Karabatak, Songul; Alanoglu, Muslim; Polat, Ebru (Institute of Electrical and Electronics Engineers Inc., 2024)
The aim of this study is to investigate the correlation between teachers' knowledge management and their knowledge hiding behaviors. The sample for this study, which was constructed using the correlational model as one of the quantitative research approaches, consists of 201 teachers selected through simple random sampling. The findings suggest that teachers demonstrate a moderate level of knowledge management, while their level of knowledge hiding behavior is low. Gender does not have a significant impact on teachers' knowledge management and knowledge hiding behaviors, although there is a significant difference in knowledge management favoring teachers in special education institution. Additionally, the study reveals a negative and moderately significant correlation between teachers' knowledge management and knowledge hiding behaviors, and no significant relationship between these variables and seniority is observed. © 2024 IEEE.
12th International Symposium on Digital Forensics and Security, ISDFS 2024 -- 29 April 2024 through 30 April 2024 -- San Antonio -- 199532
Keywords: knowledge hiding; knowledge management; teachers